Cell Viability Assays - Friedrich, Oliver; Gilbert, Daniel (2023)
This updated edition explores assessing cell viability as a measure for cell fitness under conditions of physiological and patho-physiological stress as well as challenging conditions to cellular and tissue homeostasis, and accounts for the ongoing 2D-to-3D development with topics and assays that target cell viability, mobility, and functionality of tissues and organs, natural or bioartificial, in 3D. The book’s contents span a wide range of viability and functionality assays, from impedance spectroscopy to chemiluminescence, fluorescence and label-free optical detection methodologies. Written for the highly successful Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and up-to-date, Cell Viability Assays: Methods and Protocols, Second Edition serves as a valuable resource to the growing community in bioinspired life sciences, biomedical sciences, and biotechnology by providing more standardized protocols to probe the “wellbeing” of cells in various environment
Keywords: Cell fitness; Physiological and patho-physiological stress; 2D environments; 3D assays; Cell function; Biotechnology